2018
DOI: 10.1093/schbul/sby018.861
|View full text |Cite
|
Sign up to set email alerts
|

S74. Exploring Participant-Level Trajectories of Cognitive Performance Among Patients With Schizophrenia in a Multi-National Trial

Abstract: BackgroundIt remains unclear whether the lack of clinical trial success and drug approval for cognitive impairment associated with schizophrenia (CIAS) is due to compounds being ineffective, or whether trial methodology itself has been a limiting factor in successfully demonstrating the efficacy of these agents. Schizophrenia is a heterogeneous disorder and whilst cognitive deficits are a core feature, the profile and degree of neuropsychological impairment can vary across patients. Though most individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…These findings may not generalise to other cognitive batteries. However, studies with other assessment batteries, such as the Brief Assessment of Cognition in Schizophrenia, Cambridge Neuropsychological Test Automated Battery, and MATRICS™ Consensus Cognitive Battery, have shown similar effects to those reported here, including in successful cognitive training studies [26,30].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These findings may not generalise to other cognitive batteries. However, studies with other assessment batteries, such as the Brief Assessment of Cognition in Schizophrenia, Cambridge Neuropsychological Test Automated Battery, and MATRICS™ Consensus Cognitive Battery, have shown similar effects to those reported here, including in successful cognitive training studies [26,30].…”
Section: Discussionsupporting
confidence: 70%
“…Evaluable patients were separated into two groups based on cognitive impairment at study baseline using a CBB composite Z-score cutoff of -1 SD, relative to the normative mean. This cutoff was selected based on its previous use to differentiate clinically significant cognitive impairment from non-/minimal impairment in both patients with schizophrenia and more broadly in clinical neuropsychological assessment [30][31][32]. Patients with CBB composite Z-scores equal to or above this cutoff (Z-score ≥ -1) were designated as minimally impaired, whereas patients below the cutoff (Z-score < -1) were designated as clinically impaired.…”
Section: Classification Of Impaired and Minimally Impaired Participantsmentioning
confidence: 99%
“…For the purposes of demonstrating efficacy, pro-cognitive intervention trials should be powered to detect a “clinically meaningful” difference between treatment groups, typically equating to an effect size in the small-medium range (e.g., Cohen’s d ≥ 0.3). However, recent evidence has suggested that it is unlikely that one would expect to see gains in cognition this large in up to a quarter of patients who score similarly to healthy controls on cognitive tasks (913). This means that the poorer performing patients would need to exhibit substantially greater cognitive gains in order to meet the pre-specified average group-based level of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Though the majority of patients with schizophrenia exhibit some general cognitive dysfunction compared to antecedent expectations, such as premorbid intelligence (7, 8), there is evidence that approximately a quarter of patients display cognitive performance comparable to healthy controls (912). Recent evidence has indicated that these “normally” performing patients are significantly less likely to exhibit changes in cognition when participating in CIAS trials (13, 14), suggesting that inclusion of these individuals may limit the scope to detect a pro-cognitive efficacy signal. Contemporary evidence has also reported that there is no association between cognitive performance and measures of social, vocational or everyday functioning in these cognitively “normal” patients (15), suggesting that other illness-related variables are the primary drivers of functional disability among these individuals.…”
Section: Introductionmentioning
confidence: 99%